Association of eating behaviours with diurnal preference and rotating shift work in Japanese female nurses: a cross-sectional study. Issue 11 (28th November 2016) - Yoshizaki, Takahiro; Kawano, Yukari; Noguchi, Osamu; Onishi, Junko; Teramoto, Reiko; Sunami, Ayaka; Yokoyama, Yuri; Tada, Yuki; Hida, Azumi; Togo, Fumiharu
Abstract : Objectives: Our study examines differences in eating behaviour between day workers and rotating shift workers, and considers whether diurnal preference could explain the differences. Methods: Japanese female nurses were studied (39 day workers and 123 rotating shift workers, aged 21–63 years) using self-administered questionnaires. The questionnaires assessed eating behaviours, diurnal preference and demographic characteristics. The questionnaire in the Guidelines for the management of obesity disease issued by the Japan Society for the Study of Obesity was used to obtain scores for the levels of obesity-related eating behaviours, including cognition of constitution, motivation for eating, eating as a diversion, feeling of satiety, eating style, meal contents and temporal eating patterns. The Japanese version of the Morningness–Eveningness (ME) questionnaire was used to measure self-rated preference for the degree to which people prefer to be active in the morning or the evening (ME). Results: The scores for meal contents and temporal eating patterns in rotating shift workers were significantly higher than those in day workers. The ME score of rotating shift workers was significantly lower, indicating greater eveningness/less morningness among rotating shift workers. Multivariate linear regression revealed that the ME score was significantly negatively associated with temporal eating patterns and showed a negative association with the score for meal contents at a trend level, while current work shift was not significantly correlated with the scores. Conclusions: These results suggest that eating behaviours for rotating shift workers are associated with a more unbalanced diet and abnormal temporal eating patterns and that the associations may be explained by diurnal preference rather than by rotating shift work.